Respostas

2014-05-05T13:33:38-03:00
P1 = ( 2 , 1 )  P2 = ( 7 , 1 ) e P3 = ( 3 , 8 )

distancia entre dois pontos
distancia de P1 a P2 =

 \sqrt{(x1 - x2 )^2+ (y1 - y2)^2 }  \\  \sqrt{(2-7)^2 + (1-1)^2}  \\  \sqrt{25 + 0} =5

distancia de P2 a P3
 \sqrt{(7-3)^2+(1-8)^2}  \\  \sqrt{16+49} \\  \sqrt{65}

distancia de P1 a P3
 \sqrt{(2-3)^2+(1-8)^2}  \\  \sqrt{1+49}  \\  \sqrt{50} =5 \sqrt{2}
2014-05-05T15:05:17-03:00
P1 = ( 2, 1) - Chamaremos de Ponto A
P2 = ( 7, 1) - Chamaremos de Ponto B
P3 = ( 3, 8) - Chamaremos de Ponto C

Sabendo que : 

M(Mediana) = Xa + Xb / 2 ; Ya + Yb / 2 

Mediana AB = 2+7 / 2= 9/2 ; 1+1 / 2 = 1 >>> AB (9/2 ; 1) 

Mediana BC = 7+3 / 2 = 5 ; 1+8 / 2 = 9/2 >>> BC (5 ; 9/2) 

Mediana AC = 2+3 / 2 = 5/2 ; 1+8/ 2 = 9/2 >>> AC (5/2 ; 9/2)